Virtual learning environment to improve listening skills in young students. - Siguencia Solano, Christian Enrique (2023)
The lack of resources and innovation are the biggest limitations for students when developing the Listening skills. In the present research describes the relationship that exists between the Virtual Learning Environment and the improvement of the Listening skills in young students. Likewise, the main objective of this study is analyzing the incidence of VLEs in a specific population through the data collection together with the bibliography. For the collection of data and information, a literature review and a focus group were carried out in order to compare said information and make a deduction. In the final reflections of the study, the importance of the Listening skills is reflected and why it is necessary to use the appropriate tools, in this case the VLEs. In addition, the different benefits that these offer to students and the disadvantages that could arise from improper use of these resources are described.